Od posthumanismu k hyperhumanismu - Hauser, Michael (Filosoﬁcký časopis)
Humanism is in a state of crisis, for which there are three principle reasons. The first results from theoretical criticisms from post-structuralism, feminism, postcolonialism and environmental thinking. The second flows from scientific and technological developments (biogenetics, evolutionary theory, robotics and artificial intelligence) and the third from scientific and technological capitalism. We are in a post-human time of transition that invites us to seek alternative conceptions of the human being. I introduce here an approach elaborated by Rosi Braidotti, which belongs to neo-materialist posthumanism. I acquaint the reader with Claire Colebrook’s argument that posthumanism has preserved a bias about the value of life. It is necessary to overcome it and accept the perspective of extinction. I then show the conceptual problems and ideological contradictions of these theories and propose the development of a different alternative: hyperhumanism.